Cat Product Inventory Control to Support Supply Chain Management with the Monte Carlo Method - Nabilla Safira (Journal of Computer Scine and Information Technology, 2022)
Japura Gedung Store is a store that provides quality building tools and materials. The recording of transactions at the Japura Gedung Store is only in the form of a purchase receipt. Notes from each purchase should be reprocessed to be used as information, one of which is by utilizing technology which can later be used to predict the purchase of paint products to control paint product supplies. In data processing using the Monte Carlo method with the application of Supply Chain Management . The application system built is designing a website that can provide convenience in identifying order levels with the PHP and MySQL programming languages. The data used is the historical sales of paint products from January 2022 to May 2022. From the calculation results of the Monte Carlo Method, it is obtained that the application of Supply Chain Management (SCM) and web-based Monte Carlo Simulation makes it easier for stores to manage data in a computerized manner, able to align demand and existing inventory by predicting the number of purchases in the future using Monte Carlo simulation and assisting the owner in completing the inventory at the store according to the predicted results